A cross sectional study to measure prevalence of DVT in subacute and chronic spinal cord injury patients without any chemical prophylaxis - Pande, Ashish; Gogoi, Biraj; Dubey, Sandeep; Mishra, Anil Kumar (International Journal of Research in Orthopaedics, 2019)
Background: Prevalence of DVT in patients with sub-acute and chronic SCI has only been reported in a limited number of studies. Knowing the incidence of thromboembolic events in the sub-acute and chronic rehabilitation phase is important to estimate disease risk and facilitate evidence based prevention. We sought to determine the prevalence of DVT in patients of subacute and chronic phases post spinal cord injury without any chemical prophylaxis. Methods: Between June 2016 and April 2018, all cases of sub-acute and chronic spinal cord injury, undergoing rehabilitation at our centre were studied. Patients with pre-existing coagulopathy/hypercoagulable state/ bleeding diathesis or on medications for these conditions, tobacco smokers, chronic alcoholics and obese individuals were excluded from the study. All patients enrolled in the study were given mechanical DVT prophylaxis and followed institutional rehabilitation protocol. They were evaluated at 3 months, 6 months and 9 months by clinical examination and CDFI for any evidence of DVT. Results: Out of 60 patients studied, 04 patients developed DVT (3 in ASIA grade A and 1 in ASIA grade B patient). 75% (3 cases) of the cases were detected in the first 3 months and only one case was detected between 3-6 moths post Spinal cord injury. The prevalence of DVT in our study, in subacute and chronic cases of spinal cord injury was 6.67%. Conclusions: Our study is in concurrence with the existing literature about the low prevalence of DVT in Southeast Asian population which doesn’t warrant DVT chemoprophylaxis in subacute and chronic SCI cases.